The Academic and administrative difficulties facing the faculty members of the Institute of Science and techniques of Physical Activities and Sports at Msila University. - Youcef, Hamdi (sports creativity, 2025)
This study aimed to identify the academic and administrative difficulties facing faculty member at the Institute of science and technics of physical and sports activities at Al-Messila University,In addition to identifying whether there are statistically significant differences in the responses of the study sample individuals attributed to the variables of academic rank and years of service,In this study, the researcher used the descriptive analytical method,The study population consists of the faculty members of the institute, and they are (99) members. The study sample consisted of (73) faculty members who were randomly selected,To achieve the goals of the study, the researcher prepared a Triple gradient questionnaire distributed in Two axes,The study reached a set of results, the most prominent of which were: 1 - The study sample members are in great agreement with the most important academic difficulties in the institute, the most prominent of which is (lack of seriousness among students in the learning process). 2 - The members of the study sample agree to a moderate degree on the most important administrative difficulties in the institute, the most prominent of which (the unqualified assumed various administrative positions in the institute). The results showed that there were no statistically significant differences in the responses of faculty members about: Academic and administrative difficulties facing the faculty members of the institute, according to the variable of the academic rank and years of service.